Philosophical analysis in the twentieth century. - Soames, Scott (Princeton University Press, 2003)
This is a major, wide-ranging history of analytic philosophy since 1900, told by one of the tradition's leading contemporary figures. The first volume takes the story from 1900 to mid-century. The second brings the history up to date. As Scott Soames tells it, the story of analytic philosophy is one of great but uneven progress, with leading thinkers making important advances toward solving the tradition's core problems. Though no broad philosophical position ever achieved lasting dominance, Soames argues that two methodological developments have, over time, remade the philosophical landscape.